Análisis del proceso de exportación de la empresa Bandecua S.A. del banano convencional de la provincia de El Oro - Estrada Pazmiño, Juan Carlos (2015)
The Ecuadorian banana production ranks first as exporter and second producer worldwide, for which it has been very important since its inception in the economy, with the passing of years bananas have been changes in techniques production and simultaneously improving varieties of banana exports. Bananas are grown in over 150 countries, which produce about 105 million a year, Ecuador's banana exports, representing 45.34% of the FOB value of exports and 87.14% of the tons exported. 95% of Ecuador's production is exported to 43 markets worldwide. As can be seen after the collection of data included in chapter one there is sufficient information on banana production and necessary information about the export process is why having consulted various sources point of view was obtained updated how can improve supply and demand bananas abroad. The company Bandecua S.A. exports mainly to the United States both conventional and organic bananas. The objective was to analyze the export process through the company Bandecua S.A. conventional bananas in the province of El Oro through the implementation of scientific research resulting strategies as hold bilateral meetings between Ecuador and the United States, Search non-traditional markets and Implement a permanent office negotiations, which will be of significant help to the company studied in order to improve institutional and offer the product to other countries in the world.